Beautiful accidents stories - Casocot, Ian Rosales (University of the Philippines Press, 2011)
In twelve stories collected from a decade of writing fiction, the much-awarded Dumaguete writer Ian Rosales Casocot attempts to rescue personal experience from the ephemera of travel and sexual limbo, and in the process makes his stories a fixative art, each one a grand evocation of style. "Beautiful accidents litter his stories, like glass shards from a collision... He uses language amorously, as a lover savors a kiss, so that passion becomes as real as the rhythm of his sentences," writes Timothy R. Montes of this collection of stories, where once proud fathers fade after the golden age of sugarcane in Negros, where mothers are fossilized in the celluloid memories of old movies, and where the very young play dangerous games as they hustle for sex, love, and attention in the small and weary world of university towns.